2020
DOI: 10.3390/brainsci10040247
|View full text |Cite
|
Sign up to set email alerts
|

The Supplementary Motor Area Responsible for Word Retrieval Decline After Acute Thalamic Stroke Revealed by Coupled SPECT and Near-Infrared Spectroscopy

Abstract: Damage to the thalamus may affect cognition and language, but the underlying mechanism remains unknown. In particular, it remains a riddle why thalamic aphasia occasionally occurs and then mostly recovers to some degree. To explore the mechanism of the affected cognition and language, we used two neuroimaging techniques—single-photon emission computed tomography (SPECT), suitable for viewing the affected brain distribution after acute thalamic stroke, and functional near-infrared spectroscopy (f-NIRS), focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Single-photon emission computed tomography and functional near-infrared spectroscopy suggested that FAT may play a crucial role in word retrieval difficulty in acute thalamic stroke survivors; furthermore, SMA may contribute to improve word retrieval difficulty ( 65 ). No correlation between FAT and apraxia of speech ( 66 ) or syntax ( 67 ) has been noticed.…”
Section: Discussionmentioning
confidence: 99%
“…Single-photon emission computed tomography and functional near-infrared spectroscopy suggested that FAT may play a crucial role in word retrieval difficulty in acute thalamic stroke survivors; furthermore, SMA may contribute to improve word retrieval difficulty ( 65 ). No correlation between FAT and apraxia of speech ( 66 ) or syntax ( 67 ) has been noticed.…”
Section: Discussionmentioning
confidence: 99%
“…We identified a new characteristic of disorders derived from thalamic stroke, namely “difficulty in word retrieval”, which may involve both executive function and speech production. Word retrieval disability was associated with supplementary motor area (SMA) responses, as shown by our recent f-NIRS results [12] . We focused on the association of SMA and the inferior frontal gyrus (IFG) via the frontal aslant tract (FAT) with word retrieval disability, and we will discuss the possible mechanism underlying cognitive dysfunction affected by thalamic stroke.…”
Section: Introductionmentioning
confidence: 61%
“…Our SPECT results from 16 patients in acute phase of thalamic stroke yielded diffuse cerebral perfusion abnormality in bilateral hemispheres, including the frontal cortices, superior temporal cortices, parietal cortices and cerebellum [12] . Most notably, damage to the thalamus commonly affected left language-related cortical areas and right homologous regions, including Broca's area (left 44, 45), Wernicke's area (22, 42), angular gyrus (39), and supramarginal gyrus (40).…”
Section: Word Retrieval Difficulty Due To Thalamic Stroke and Neural ...mentioning
confidence: 67%
See 1 more Smart Citation
“…Other studies of speech processing after stroke have also reported enhanced SMA activation during overt speech production in patients with left inferior frontal lesions ( Rosen et al, 2000 ) and during the recovery of speech comprehension in patients with a range of different left hemisphere lesions ( Stockert et al, 2020 ). Likewise, Obayashi (2020) reported that SMA activation was higher in patients with thalamic lesions who had better verbal fluency. Additionally, enhanced SMA activation after stroke is not limited to speech tasks.…”
Section: Discussionmentioning
confidence: 95%